Shariah-Compliant Investment Funds: A Study on Investor Preferences and Portfolio Management in Indonesia - Tanaka, Kaito; Sato, Haruko; Amlia, Nilam (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Shariah-compliant investment funds have gained significant traction in Indonesia, driven by the growing demand for ethical and religiously aligned financial products. However, limited research exists on investor preferences and portfolio management strategies specific to these funds, particularly in the context of Indonesia’s dynamic Islamic finance market. This study explores the factors influencing investor preferences for Shariah-compliant funds and examines the portfolio management strategies employed by fund managers to align with Shariah principles. The research aims to provide insights into how Shariah-compliant funds can better meet investor expectations while maintaining compliance with Islamic principles. Using a mixed-methods approach, this study combines surveys of individual and institutional investors with interviews of fund managers and Shariah advisors. Data were analyzed to identify key preferences, such as risk tolerance, return expectations, and ethical considerations, as well as the challenges faced by fund managers in balancing Shariah compliance with financial performance. The findings reveal that investors prioritize ethical alignment and transparency, while fund managers emphasize diversification and adherence to Shariah screening criteria. The study concludes that Shariah-compliant funds in Indonesia must adopt innovative portfolio management strategies to attract a broader investor base while ensuring strict compliance with Shariah principles. This research contributes to the growing body of knowledge on Islamic finance by providing practical recommendations for fund managers and policymakers to enhance the competitiveness and appeal of Shariah-compliant investment funds.